2018
DOI: 10.2147/ott.s153946
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of serum total oxidant/antioxidant status in patients with operable and advanced gastric cancer

Abstract: PurposeOxidative stress was significantly associated with the development of malignancies. The purpose of this study was to evaluate the significance of serum total oxidant/antioxidant status in operable advanced gastric cancer patients.Materials and methodsA total of 284 patients who underwent curative resection for primary stage III gastric cancer were enrolled. Total oxidant status, total antioxidant status, and oxidative stress index (OSI) were evaluated within 24 hours before surgery, and compared with 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…This means the lack of antioxidant system in IM similar to proliferative processes. A recently published study revealed that total antioxidant status was lower in patients with gastric cancer than controls, and unsurprisingly total oxidant status was greater in gastric cancer patients (16). There is more evidence in the literature for increased radical oxygen species in the gastric cancer (17).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This means the lack of antioxidant system in IM similar to proliferative processes. A recently published study revealed that total antioxidant status was lower in patients with gastric cancer than controls, and unsurprisingly total oxidant status was greater in gastric cancer patients (16). There is more evidence in the literature for increased radical oxygen species in the gastric cancer (17).…”
Section: Discussionmentioning
confidence: 99%
“…Strengths of our study are as follows: 1) according to our knowledge this is the first study investigating the antioxidant system in IM, although it was investigated in previous studies in gastric cancer [16] [17] [18] . Second, our control group were similar in terms of demographic and co morbid features; third, the blood samples taken from control and patient group were kept at similar durations, hence minimizing the factors that may affect the study in order to provide more refined data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hepatocellular carcinoma (HCC) is claimed to be one kind of the most common malignancy in background with a high morbidity of hepatitis virus infection, which is also the third commonest cause of cancer-associated mortality in China for its aggressive recurrence and metastasis ( 1 - 4 ). Despite advancement of adjunctive treatment, surgery and transplantation have taken benefits for HCC patients over decades, the survival outcome of HCC still be unsatisfactory with main contributors of relapse or metastasis, especially for patients complicated with severe cirrhosis ( 5 - 7 ).…”
Section: Introductionmentioning
confidence: 99%